Apply the distributive property to create an equivalent expression. 4\left(3 + \dfrac14c - \dfrac12d\right) =4(3+ 4 1 ​ c− 2 1 ​ d)=

Respuesta :

Answer:

The equivalent expression is [tex]12+c-2d[/tex]

Step-by-step explanation:

Using the distributive property we expand the expression

[tex]4\left(3 + \dfrac14c - \dfrac12d\right)[/tex]

as follows:

[tex]4\left(3 + \dfrac14c - \dfrac12d\right)=(4*3)+(4*\dfrac{1}{4} c)-(4*\dfrac{1}{2} d)[/tex]

[tex]=(12)+(c)-(2d)[/tex]

[tex]=\boxed{ 12+c-2d}[/tex]

which is the equivalent expression.

answer   =   12+c-2d

                  .......................................................